SAT0098 Cox-2 specific inhibitors – is there any benefit of using these agents in patients on low dose aspirin (asa)?. (1st June 2001) - Singh, G; Goldstein, J; Agrawal, N; Eisen, G; Stenson, W; Fort, J; Bello, A; Boots, S
Abstract : Background: COX-2 specific inhibitors have been shown to significantly reduce the risk of gastrointestinal complications compared to conventional NSAIDs, while providing equivalent efficacy. However, there is significant controversy regarding the UGI safety and tolerability benefits of COX-2 specific inhibitors, such as celecoxib, in patients on concomitant low-dose ASA ( <325 mg/day) for cardiovascular protection. Objectives: To evaluate the UGI tolerability and safety of celecoxib 200 or 400 mg per day and the commonly prescribed conventional NSAIDs (diclofenac or naproxen) in patients taking ASA in SUCCESS-1, a large multinational double-blind, randomised study. Methods: SUCCESS-1 enrolled 13, 274 patients from 1, 142 centres in 39 countries in Europe and South Africa, Asia, Latin America, and the US and Canada. Patients were treated for 12 weeks using celecoxib (200 or 400 mg/d) and NSAIDs (naproxen 1000 mg/d in US and Canada and diclofenac 100 mg/d in all other countries). Adverse events were captured at week 6 and week 12 using standard adverse assessment ascertainment. In addition, all investigator-identified potentially clinically significant UGI events were referred to an independent Gastrointestinal Events Committee (GEC), which reviewed all data in a blinded fashion. Events were categorised as UGI ulcer complications (perforations, gastric outlet obstruction, bleeding), symptomatic UGI ulcerations or other GI events. Results: Of the 13, 194 patients randomised in the SUCCESS-1 trial, 4421 and 4429 patients received 200 or 400 mg per day of celecoxib respectively, 914 patients received 1000 mg per day of naproxen, and 3510 patients received 100 mg per day of diclofenac. Patients were mostly female (67%), and 42% were 65 years or older (mean age: 62 years). Patients in each group had comparable baseline aspirin use and past history of upper GI (UGI) bleeding. A total of 697 patients took celecoxib and ASA. In the NSAID arm, 348 patients took concomitant ASA. Conclusion: Risk reduction with celecoxib and ASA is lower than risk reduction in patients not taking ASA. However, the magnitude of this risk reduction is clinically significant. Therefore, celecoxib continues to have a role in reducing risk of UGI complications even in patients on low dose ASA.